2013
DOI: 10.14419/ijbas.v3i1.1467
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of stature from combined length of forearm and hand in Jammu region of India

Abstract: Estimation of stature is a major cause of concern in forensic medicine and forensic anthropology. It becomes difficult to predict the physical identification of an individual when only fragmentary remains of dead body are brought for postmortem. Physical reconstruction from such remains depends upon the fact that various body parts exhibit consistent ratios when compared to total height of a person. Present study is an endeavor to generate formula for estimation of stature from combined length of forearm and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In some studies, where different body parameters have been used to predict body height, arm span has been shown to be the most reliable predictor of body height (Arifi, 2018), while hand length is a more reliable predictor of body height during adolescence, since shorter bone growth ends sooner than long bone growth (Amirsheybani et al, 2000). Some contemporary scholars have attempted to estimate body height by combining forearm and fist lengths, and have found that height assessment is a major cause of controversy and research in forensics and anthropology (Choudhary et al, 2014). Positive correlation have been found between body height and hand length in different populations and a regression coefficient has been offered (Varu et al, 2015), however, the regression formula in one population is not always unique to another population and studies indicate the need to study population specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, where different body parameters have been used to predict body height, arm span has been shown to be the most reliable predictor of body height (Arifi, 2018), while hand length is a more reliable predictor of body height during adolescence, since shorter bone growth ends sooner than long bone growth (Amirsheybani et al, 2000). Some contemporary scholars have attempted to estimate body height by combining forearm and fist lengths, and have found that height assessment is a major cause of controversy and research in forensics and anthropology (Choudhary et al, 2014). Positive correlation have been found between body height and hand length in different populations and a regression coefficient has been offered (Varu et al, 2015), however, the regression formula in one population is not always unique to another population and studies indicate the need to study population specificity.…”
Section: Introductionmentioning
confidence: 99%
“…stature, body weight). Several studies support the relationship between gender, BM and BH, and the footprint pattern [11], [12], [13], [14], [15]. However, most of the studies analyses pre-historic footprints on 2D features (length and width) [16].…”
Section: Introductionmentioning
confidence: 99%